2006
DOI: 10.1002/bjs.5424
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis comparing suprapubic and transurethral catheterization for bladder drainage after abdominal surgery

Abstract: The suprapubic route for bladder drainage in general surgery is more acceptable to patients and reduces microbiological morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(50 citation statements)
references
References 14 publications
2
44
0
1
Order By: Relevance
“…In general, their use is not warranted. Subgroup analyses for the variability in the texture and duct size of the pancreas are not available Evidence level Moderate Recommendation grade Strong Urinary drainage A meta-analysis of RCTs on urinary drainage after surgery showed that suprapubic catheterisation was superior to transurethral catheterisation [167]. Patients found suprapubic catheters more acceptable, and morbidity was reduced [167].…”
Section: Summary and Recommendationmentioning
confidence: 99%
“…In general, their use is not warranted. Subgroup analyses for the variability in the texture and duct size of the pancreas are not available Evidence level Moderate Recommendation grade Strong Urinary drainage A meta-analysis of RCTs on urinary drainage after surgery showed that suprapubic catheterisation was superior to transurethral catheterisation [167]. Patients found suprapubic catheters more acceptable, and morbidity was reduced [167].…”
Section: Summary and Recommendationmentioning
confidence: 99%
“…A meta-analysis of patients undergoing laparotomy also showed that patients with urethral catheterization are more likely to experience substantial bacteriuria and pain or discomfort than patients undergoing suprapubic cystostomy. 11 Tewari et al 12 reported patients undergoing RALP with a specialdesigned double balloon suprapubic catheter that passes through the anastomosis into the urethra. There was substantially less penile shaft or tip pain and discomfort in the study group.…”
Section: Discussionmentioning
confidence: 99%
“…It also enables patients, especially males to attempt normal voiding [2][3][4][5]. There is evidence to suggest that SPC are more acceptable to patients [3,4,6], with one study suggesting that 89% prefer SPC to urethral catheters [1]. We present a case of elective percutaneous insertion of a SPC which resulted in significant intra-abdominal haemorrhage and bowel injury, requiring emergency laparotomy, intensive care admission, prolonged hospitalisation and extensive rehabilitation.…”
Section: Introductionmentioning
confidence: 95%
“…Compared with urethral catheterisation, SPC is associated with a superior quality of life, reduced infection rates and less pain and discomfort. It also enables patients, especially males to attempt normal voiding [2][3][4][5]. There is evidence to suggest that SPC are more acceptable to patients [3,4,6], with one study suggesting that 89% prefer SPC to urethral catheters [1].…”
Section: Introductionmentioning
confidence: 99%